Order and anarchy : civil society, social disorder and war - Layton, Robert, 1944- (Cambridge University Press, 2006)
Studying civil society, the evolution of social relations, and the breakdown of social order, Order and Anarchy re-examines the role of violence in human social evolution. Drawing on anthropology, political science, and evolutionary theory, it offers a novel approach to understanding stability and instability in human society.